Inverting the flexicurity paradigm: the United Kingdom and zero hours contracts - Kenner, Jeff (Hart Publishing, 2017)
Labour and social security law studies have addressed the topic of the decline of the standard employment relationship mainly from the point of view of the growing number of atypical relationships. Only a limited number of studies have examined the issue from the perspective of the differentiation between core and contingent work. Such an examination is necessary as the increase in contingent work leads to complicated legal questions which vary between European states depending on the type of contingent arrangements that have become most prevalent. This book analyses, using a comparative approach, these different types of contingency from a national and EU perspective touching on the work relationship from a labour as well as a social security point of view. The aim of the book is to identify and analyse those questions adopting an innovative approach and to put forward proposals for safeguarding social cohesion within undertakings and European society.